2016
DOI: 10.3109/10520295.2016.1164897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of L-cysteine on lead acetate induced neurotoxicity in albino mice

Abstract: Lead is a toxic heavy metal that adversely affects nervous tissues; it often occurs as an environmental pollutant. We investigated histological changes in the cerebral cortex, hippocampus and cerebellum of adult albino mice following exposure to lead acetate. We also studied the possible ameliorative effect of the chelating agent, L-cysteine, on lead-induced neurotoxicity. We divided albino mice into six groups: 1) vehicle-only control, 2) L-cysteine control, 3 and 4) treated for 7 days with 20 and 40 mg/kg le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…2I. The PbAc dose (40 mg/kg body weight "bw") was chosen and given intraperitoneally (ip)according to previous study 77 . The BVJ dose ("1 g BVJ dissolved in distilled water/kg bw = 8 mL juice/kg bw, where 1 g of BVJ contains 17.26 mg galic acid equivalent as total phenolic compounds) was chosen and given orally using oral cavage according to the previous study 78 .…”
Section: Investigation Of the Phytochemical Compositions Of Bvj Usingmentioning
confidence: 99%
“…2I. The PbAc dose (40 mg/kg body weight "bw") was chosen and given intraperitoneally (ip)according to previous study 77 . The BVJ dose ("1 g BVJ dissolved in distilled water/kg bw = 8 mL juice/kg bw, where 1 g of BVJ contains 17.26 mg galic acid equivalent as total phenolic compounds) was chosen and given orally using oral cavage according to the previous study 78 .…”
Section: Investigation Of the Phytochemical Compositions Of Bvj Usingmentioning
confidence: 99%
“…Also lightly stained Nissl and numerous chromatolytic cells were observed. Several earlier studies had reported the ability of Pb to cause neuronal degeneration, chromatolysis and distortion of cortical layers [39][40][41][42]. This result indicates that the number of healthy neurons available to carry out normal function within the DLPFC will be low, thereby affecting is the function in working memory (Figure 1).…”
Section: Discussionmentioning
confidence: 92%
“…Group I was given deionised water and served as the control group. Group II received 40 mg/kg bw of lead acetate according to Mahmoud et al [22] Group III received 40 mg/kg bw of lead acetate and 1 mL/kg bw of honey according to Abdulmajeed et al [23] Group IV received 40 mg/kg bw of lead acetate and 100 mg/kg of Vitamin C according to Li et al [24] Group V received 40 mg/kg bw of lead acetate, 1 mL/kg bw honey, and 100 mg/kg bw of Vitamin C. All treatments were coadministered with lead acetate orally for a period of 28 days according to Abdulmajeed et al [23]…”
Section: Animal Groupingmentioning
confidence: 99%